Hydrothermally treated coals for pulverized coal injection. Final technical report - Walsh, D.E.; Rao, P.D.; Ogunsola, O.; Lin, H.K. (University of Southern California, Los Angeles, CA (United States). Law Center, 1995)
This project investigated the suitability of hydrothermally dried low-rank coals for pulverized fuel injection into blast furnaces in order to reduce coke consumption. Coal samples from the Beluga coalfield and the Usibelli Coal Mine, Alaska, were used for the study. Crushed coal samples were hydrothermally treated at three temperatures, 275, 300 and 325degreesC, for residence times of 10, 60 and 120 minutes. Products were characterized to determine their suitability for pulverized coal injection. Characterization included proximate and ultimate analyses, vitrinite reflectance and TGA reactivity. A literature survey was also conducted.